Beejal is solving the equation  y/7 − 3 = 39

1 answer

To solve the equation, we need to isolate the variable y.

First, we can add 3 to both sides of the equation to eliminate the -3 on the left side:
y/7 - 3 + 3 = 39 + 3
This simplifies to:
y/7 = 42

Next, to eliminate the fraction, we can multiply both sides of the equation by 7:
7 * (y/7) = 42 * 7
This simplifies to:
y = 294

So, the solution to the equation is y = 294.
Similar Questions
  1. beejal is solving the equation y/7 - 3 = 39as a first step, he starts by adding to both sides of the equation, and then
    1. answers icon 1 answer
  2. Beejal is solving the equation y7 − 3 = 39.(1 point)As a first step, he starts by adding to both sides of the equation, and
    1. answers icon 2 answers
    1. answers icon 1 answer
  3. Tillie is solving an equation for x. Her first step is to subtract 8 from both sides of the equation. Which equation is she
    1. answers icon 3 answers
more similar questions